Evidence for Plio-Pleistocene Duck Mussel Refugia in the Azov Sea River Basins - Alena A. Tomilova; Artem A. Lyubas; Alexander V. Kondakov; Ilya V. Vikhrev; Mikhail Y. Gofarov; Yulia S. Kolosova; Maxim V. Vinarski; Dmitry M. Palatov; Ivan N. Bolotov (Diversity, 2020)
Freshwater mussels (Bivalvia: Unionoida) play an important role in freshwater habitats as ecosystem engineers of the water environment. Duck mussel Anodonta anatina is widely distributed throughout Europe, Siberia, and Western and Central Asia, which makes it a convenient object for biogeographic studies. In this study, we analyzed the divergence of A. anatina populations and discovered a separate genetic lineage distributed in rivers of the Azov Sea basin. This was confirmed by the high genetic distances between this group and previously defined populations, and by the position of this clade in the Bayesian phylogeny calibrated by an external substitution rate. Based on our approximate Bayesian computation (ABC) analysis, biogeographic scenarios of A. anatina dispersal in Europe and Northern, Western, and Central Asia over the Neogene−Quaternary were simulated. The haplogroup’s isolation in the rivers of the Azov Sea basin most likely occurred in the Late Pliocene that was probably facilitated by rearrangement of freshwater basins boundaries in the Ponto-Caspian Region. Population genetic indices show the stability of this group, which allowed it to exist in the river basins of the region for a long time. The discovery of a long-term refugium in the rivers of the Azov Sea led to a better understanding of freshwater fauna evolution in the Neogene−Quaternary and highlighted the importance of conservation of these freshwater animals in the region as a source of unique genetic diversity.